2019
DOI: 10.1093/cvr/cvz200
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for people living with heart failure: European Association for Palliative Care Task Force expert position statement

Abstract: Contrary to common perception, modern palliative care (PC) is applicable to all people with an incurable disease, not only cancer. PC is appropriate at every stage of disease progression, when PC needs emerge. These needs can be of physical, emotional, social, or spiritual nature. This document encourages the use of validated assessment tools to recognize such needs and ascertain efficacy of management. PC interventions should be provided alongside cardiologic management. Treating breathlessness is more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(176 citation statements)
references
References 197 publications
3
150
0
5
Order By: Relevance
“…The results of this review are concordant with the recent European Association for Palliative Care (EAPC) position statement where a comprehensive palliative care needsassessment tool was suggested to identify patients with unmet needs [9]. NAT:PD-HF, being validated for patients with heart failure, was suggested as an example of such a tool but this was not based on detailed comparisons with other tools.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results of this review are concordant with the recent European Association for Palliative Care (EAPC) position statement where a comprehensive palliative care needsassessment tool was suggested to identify patients with unmet needs [9]. NAT:PD-HF, being validated for patients with heart failure, was suggested as an example of such a tool but this was not based on detailed comparisons with other tools.…”
Section: Discussionsupporting
confidence: 65%
“…The choice of the most appropriate tools was based on comprehensive comparisons according to predetermined criteria. Although NAT:PD-HF was suggested as an example of a good needs-assessment tool in the EAPC statement and another review, this was not based on such comparisons [9,18].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 2010 publication of the EHRA and the HRA statements, others have also recommended discussing implantable cardioverter defibrillator reprogramming in patients nearing the end of life. 2,30 Although protocols now guide physicians and healthcare providers through the deactivation process step by step, 31,32 our review found only a 28% pooled prevalence of implantable cardioverter defibrillator reprogramming at the end of life. Across studies, prevalence ranged from 15% to 52%, and almost all of the device reprogramming happened in a hospital setting, with fewer in hospices and nursing homes, and very few in patients at home.…”
Section: Main Findingsmentioning
confidence: 89%
“…This last point is essential, as palliative care is frequently suboptimal in elderly patients with other conditions, such as heart failure, and this is probably the case in COVID-19. 2,9,10…”
Section: Covid-19 and The Elderlymentioning
confidence: 99%